The performance of structured cobalt catalysts in Fischer-Tropsch synthesis - Zhuang, Youqi (Department of Chemical Engineering, 2014)
Cobalt is the preferred catalyst metal for the production of clean burning, high cetane number diesel fuel from synthesis gas using the Fischer-Tropsch synthesis. Hence, increasing C5+ selectivity of cobalt catalysts is one of the hot topics in Fischer-Tropsch synthesis. Internal mass transport limitation may affect C5+ selectivity. It was concluded that mild transport limitation is required for maximum C5+ selectivity. Mild transport limitation also increases the catalyst activity, since the reported Fischer- Tropsch rate of reaction has a negative dependency on CO partial pressure. The metal distribution within catalyst pellets may modify product selectivity by changing the local metal density and the diffusion path length. However, current catalyst preparation methods limit metal distribution in transition metal catalysts. The aim of this study is to explore a possible catalyst synthesis route for egg-shell, egg-yolk and egg-white type of cobalt catalyst pellets. The establishment of the nonuniform cobalt catalyst synthesis method will provide an observational evaluation technique for the investigation of the effect of intra-pellet metal distribution on the activity and product selectivity of the Fischer-Tropsch synthesis. The non-uniform catalyst synthesis method utilises the hydrophobic nature of the silica pellet. Egg-shell, egg-yolk and egg-white type of cobalt catalyst with sharp metal enriched boundary were synthesized. The intra-pellet cobalt distribution, metal particle size, metal loading, metal surface area and catalyst reducibility were characterised. The performance of these non-uniform catalysts was tested in a modified slurry type reactor. Catalyst pellets were kept in mesh-wire baskets which were mounted inside a slurry reactor, and tested in the absence of external mass transport limitation. The Fischer-Tropsch activity was recorded and modelled using a reaction-diffusion pellet inside a continuous stirred tank reactor model. The product selectivity were analysed with an offline GC. The Fischer-Tropsch activity is strongly dependent on the intra-pellet metal distribution. The egg-shell type of catalyst outperforms the uniform, egg-yolk and eggwhite type of catalyst, in terms of activity, under the influence of internal mass transport limitation. The intra-pellet distribution alters the reactant concentration in the pellet as well as intra-pellet H2/CO ratio. The reaction-diffusion path length was identified to be a suitable parameter for product selectivity. An increase in the reaction-diffusion path results in an increase in -olefins re-adsorption, a decrease in olefin content and an increase branched product compounds. Secondary chain growth is not favoured under internal mass transport limitation.